Attitudes toward uncertainty and randomization: an experimental study - Dominiak, Adam; Schnedler, Wendelin (Economic theory, 2011)
Subjects are randomization-loving if they prefer random mixtures of two bets to each of the involved bets. Various approaches appeal to such preferences in order to explain uncertainty aversion. We examine the relationship between uncertainty and randomization attitude experimentally. Our data suggest that they are not negatively associated: most uncertainty-averse subjects are randomization-neutral rather than loving. Surprisingly, a non-negligible number of uncertainty-averse subjects even seems to dislike randomization.
Gesehen am 20.06.2022